The molecular classification ushers in a new era for the treatment of advanced and recurrent endometrial cancer - Yan, Liwei; Ding, Xiaoxu; Deng, Yuanmei; Li, Yachai; Du, Xiaoxin (Frontiers in Oncology, 2026)
Endometrial cancer is among the most common malignant tumors of the female reproductive system, with an increasing incidence globally over the past decade and ranking first among gynecological malignancies in developed countries. Although early-stage prognosis is favorable, the mortality rate of advanced and recurrent endometrial cancer remains high, posing a significant clinical challenge. Molecular classification systems, such as TCGA and ProMisE, have identified four distinct molecular subtypes: POLE-mutant (POLEmut), mismatch repair-deficient (MMRd), no specific molecular profile (NSMP), and p53-abnormal (p53abn), each exhibiting significantly different biological behaviors, recurrence patterns, and treatment responses. “Chemotherapy-free” strategies show potential for specific subtypes and offer new avenues for reducing toxicity. Faced with challenges, such as tumor heterogeneity and drug resistance mechanisms, future research should focus on optimizing standardized molecular classification protocols, exploring novel combination therapies, and integrating real-world evidence. A personalized treatment system centered on molecular classification that considers the quality of life and treatment accessibility is crucial for precision medicine in advanced and recurrent endometrial cancer.